Determination of the b̄→d*ℓv̄ decay width and |Vcb| - Adam, N; Alexander, J; Bebek, C; Berger, B; Berkelman, K; Blanc, F; Boisvert, V; Cassel, D; Drell, P; Duboscq, J; Ecklund, K; Ehrlich, R; et al. (2003)
In the standard model, the charged current of the weak interaction is governed by a unitary quark mixing matrix that also leads to CP violation. Measurement of the Cabibbo-Kobayashi-Maskawa (CKM) matrix elements is essential to searches for new physics, either through the structure of the CKM matrix, or a departure from unitarity. We determine the CKM matrix element |Vcb| using a sample of 3 × 106 BB̄ events in the CLEO detector at the ornell Electron Storage Ring. We determine the yield of reconstructed B̄0 →D*+ℓv̄ and B-→D*0ℓv̄ decays as a function of w, the boost of the D* in the B rest frame, and from this we obtain the differential decay rate dΓ/dw. By extrapolating dΓ/dw to w = 1, the kinematic end point at which the D* is at rest relative to the B, we extract the product |Vcb|F(1), where F(1) is the form factor at w = 1. We find |Vcb|F(1) = 0.0431±0.0013(stat) ±0.0018(syst). We combine |Vcb|F(1) with theoretical results for F(1) to determine |Vcb| = 0.0469±0.0014(stat)±0.0020)syst)±0.0018(theor). We also integrate the differential decay rate over w to obtain B(B̄0→D*+ℓv̄) = (6.09±0.19±0.40)% and B(B-→D*0ℓv̄) = (6.50±0.20±0.43)%.